Implementation of photovoltaics in Malaysia - Mohamad A.A.S.; Pasupuleti J.; Shamsuddin A.H. (2023)
This paper aims to explore the viability of photovoltaic (PV) systems in Malaysia. The Malaysian Energy Center (PTM)'s Suria1000 project highlights the problems associated with rooftop PV systems. TNB's off-grid PV projects also provide valuable lessons on standalone PV systems. PTM's Building Integrated Photovoltaic (BIPV) project shows grid-connected rooftop PV systems are viable. The annual energy output of these installations has been found to be in the top 50 % of similar installations Worldwide. The major obstacles to these systems are the high capital cost of the system and the absence of a feed-in tariff. TNB's experience with offgrid PV projects point to their viability as an attractive alternative to costly extension of the grid for small isolated loads. The major problem is the high maintenance cost of these installations. Simulation studies indicate that standalone PV systems with storage capacity and backup generator are cheaper than grid extension for small loads beyond a certain distance from the grid. Rooftop PV generation in the commercial areas of the city can also be an attractive alternative to upgrading the existing grid capacity. The study concludes that various PV system options need to be introduced into the country on an urgent basis to bring down capital and maintenance costs as well as provide learning opportunities to upgrade the technical competencies of its human resource. 2009 IEEE.